Evaluation of the effectiveness of the personnel management system - Alevtina Pakulina (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
The article discusses the main functions of personnel management, the main tasks of analysis and planning of personnel costs. The goal of personnel cost management is to ensure a balance between costs and results. This will allow, on the one hand, to pay off the content of the hired workforce, and on the other hand, to solve social tasks – to achieve staff satisfaction with work at this enterprise, the development of such important personnel qualities as involvement, dedication, innovative activity, etc. It was established that the organization’s personnel management is a purposeful activity of the organization’s management, managers and specialists of personnel management system units, which includes the development and implementation of the concept and strategy of the personnel policy, principles and methods of the organization’s personnel management. The achievement of the goal of personnel management is its personnel technology. Personnel-technology is the managerial influence of the subject of management with the aim of implementing the desired transformations of the internal labor market (number, structure, competence, personnel costs), aimed directly at the employee or at their group as a production center, or at the factors of the internal and external environment, in which the work process takes place. In other words, it is necessary to distinguish two groups of personnel technologies in the most general way – personnel management technologies and personnel work (personnel management) technologies. The process of developing ways to achieve consistency between two groups of personnel technologies – personnel management and personnel management – has gained further development. This is a joint discussion of problems and development of joint personnel solutions; clear separation of powers, rights and responsibilities between line, functional managers and personnel service specialists; learning mutual understanding and cooperation through rotation, transfer from personnel services to line managers, and vice versa. We suggest using in practical activities an indicator that characterizes the ratio of costs for achieving economic priorities and social goals (achieving economic and social results). This ratio can be used to establish social norms. Such social norms (their system) can be used in the assessment of the social performance of the enterprise, the degree of solving social tasks facing management personnel. To plan personnel costs, it is suggested to use indicators of salary intensity and salary return.